PENGARUH BERMAIN FACE NUMBER TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 3 KOTA PEKANBARU - Rosrita Rosrita; Zulkifli N Zulkifli N; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: based on the result of observation on the ability to know the concept of numbers of young learners has not developed optimally. So it is necessary to implement the activity play face number. The objective of this research is to find out the effect of play face number on the ability to know the concept of numbers of children age 4-5 years at pembina 3 kindergarten, pekanbaru with one group pretest posttest design is an experiment that do by one group only without comparison. The sample in this research are 15 young learners. The kind of the instrument that used in this research is observation sheet and documentation to noted about activities that happen during the treatment is given. Based on the result of hypothesis there is an effect of play face number on the ability to know the concept of numbers of children age 4-5 years at pembina 3 kindergarten, pekanbaru. The value of thitung is 11.129 with sig 0.000, because sig < 0.05 it can be concluded that there is a significant difference on the ability to know the concept of numbers of children age 4-5 years before and after applied play face number on the lesson. On the hypothesis it can be seen that thitung = 11.129> t table= 2.145. it can be concluded that there is siginificant different result between pretest and posttest. the effect of play face number on the ability to know the concept of numbers of children age 4-5 years at pembina 3 kindergarten, pekanbaru.Keywords: Play Face Number, The Concept Of Numbers.